Educational Status of Thami Children in Lalbandi Municipality - Ghimire, Dharma Raj (Janajyoti Journal, 2024)
Thamis are one of the ethnic groups residing in 37 districts of Nepal. They are one of the most marginalized ethnic groups in Nepal. Their educational status is a rare topic of the researches. There are 32,743 Thami people living in Nepal as of the 2021 AD population census. Regarding the total number of Thami residents in Lalbandi Municipality, there are 267 of them in all, living in 63 dwellings in wards 13 and 15. The main purpose of the present study was to determine the existing educational status of Thami children residing in Lalbandi Municipality as well as the different factors influencing their academic performance. Housewives from Thami families, students enrolled in schools, teachers, school principals, and concerned ward representatives make up the study’s respondents. In a similar vein, the instruments used for gathering data included questionnaires, interviews, and observations. Primary data was first gathered by the researcher, followed by secondary data, and finally a descriptive analysis of the data was employed. Moreover, it was found through data analysis that while the number of Thami children enrolled in schools has increased, their overall academic performance is not still satisfactory. Furthermore, it is found that the efforts of different stakeholders are not adequate to improve their educational status. Therefore, the concerned authorities ought to employ better strategies for the academic excellence of the Thami children.